Pengaruh Asset Turnover, Return On Asset Dan Return On Equity Terhadap Kinerja Lingkungan Berbasis Peringkat Proper: Studi Kasus Pada Perusahaan LQ45 Di Bursa Efek Indonesia Periode 2011-2013 - Yusuf, Felicia; Widayanti, Rita; Colline, Fredella (Ilmiah Manajemen Bisnis, 2015)
ÃÂ ABSTRACTThis study examined the effect of Asset Turnover Return on Asset and Return on Equity on environmental performance based on PROPER in LQ45 companies on period 2011-2013. Asset Turnover, ROA and ROE are the ratio used by the company in assessing the financial performance of companies while PROPER is a measure of environmental performance provided by the Ministry of Environmental RI. Asset turnover is a ratio that measures the turnover of all assets owned by the company. ROA is the ratio that measures a companyÃ¢â¬â¢s ability to generate profits from investing activities. ROE is the ratio that measures the net profit earned from the management of the capital invested by the owner of the company. The results of this study will answer the research question is whether there is influence between Asset Turnover. ROA and ROE for the PROPER environmental performance. Results obtained from the processing of data by the number of 42 samples are asset turnover has significant effecr on environmental performance PROPER but ROA and ROE has no effect on environmental performance PROPER. ÃÂ Keywords: Asset Turnover, ROA, ROE, PROPER, LQ45ABSTRACTPenelitian ini menguji pengaruh antara Asset Turnover, Return on Asset dan Return on Equity terhadap Kinerja Lingkungan yang berbasis PROPER pada Perusahaan LQ45 periode 2011-2013. Asset Turnover, Return on Asset dan Return on Equity merupakan rasio yang digunakan perusahaan dalam menilai kinerja keuangan yang dimiliki oleh perusahaan, sedangkan PROPER merupakan alat ukur kinerja lingkungan yang disediakan oleh Kementrian Lingkungan Hidup RI. Asset Turnover adalah rasio yang mengukur perputaran dari seluruh Aset yang dimiliki oleh perusahaan. Return on Asset adalah rasio yang mengukur kemampuan perusahaan dalam menghasilkan laba yang berasal dari investasi. Return on Equity adalah rasio yang mengukur keuntungan bersih yang diperoleh pemilik perusahaan. Masalah penelitian adalah apakah terdapat pengaruh antara Asset Turnover, Return on Asset dan Return on Equity terhadap kinerja lingkungan PROPER. Hasil penelitian adalah terdapat pengaruh siginifikan antara Asset Turnover terhadap kinerja lingkungan PROPER, namun Return on Asset dan Return on Equity tidak berpengaruh terhadap kinerja lingkungan PROPER.Keywords: Asset Turnover, ROA, ROE, PROPER,LQ45